Multisubunit tethering complexes in higher plants. (December 2017) - Ravikumar, Raksha; Steiner, Alexander; Assaad, Farhah F
Highlights: Multisubunit tethering complexes (MTCs) can exist in a variety of modular forms. Plant MTCs interact with small GTPases, SNAREs and Sec1/Munc18 proteins. Plant MTC–MTC interactions mediate cell plate progression–maturation. Plant MTCs may be direct targets of pathogen effectors or virulence factors. Abstract : Tethering complexes mediate the initial, specific contact between donor and acceptor membranes. This review focuses on the modularity and function of multisubunit tethering complexes (MTCs) in higher plants. One emphasis is on molecular interactions of plant MTCs. Here, a number of insights have been gained concerning interactions between different tethering complexes, and between tethers and microtubule-associated proteins. The roles of tethering complexes in abiotic stress responses appear indirect, but in the context of biotic stress responses it has been suggested that some tethers are direct targets of pathogen effectors or virulence factors. In light of the central roles tethering complexes play in plant development, an emerging concept is that tethers may be co-opted for plant adaptive responses.